APPLICATION OF HIGH-RESOLUTION ELECTRON-ENERGY-LOSS SPECTROSCOPY TO MBE GROWN GAAS(100) - Graygrychowski, Z; Egdell, R; Joyce, B; Stradling, R; Woodbridge, K (1987)
Plasmon and phonon modes of silicon-doped MBE grown (100) oriented GaAs (n≈4×1018/cm3) have been observed by high-resolution electron-energy-loss spectroscopy (HREELS). A protective arsenic overlayer allowed transfer of samples from the MBE growth chamber to the HREELS system without contamination of the underlying GaAs. Criteria are presented which allow appraisal of the success or failure of the arsenic desorption procedure used to prepare clean, ordered sample surfaces. The variation of intensity and energy of the loss features with exciting beam energy are analysed in terms of a model which incorporates a carrier free surface depletion layer on top of the undepleted bulk. © 1987 Elsevier Science Publishers B.V.